DETERMINANTS ANALYSIS OF STUNTING PREVALENCE AMONG TODDLERS IN CENTRAL JAVA PROVINCE IN 2022 - Prayogi, Dicki; Rini Rahani (Jurnal Statistika dan Aplikasinya, 2024)
Stunting is a chronic malnutrition condition that results in toddlers being too short for their age. The World Bank (2020) reported that 54 percent of Indonesia's workforce comprises stunting survivors. This can pose a serious threat to the achievement of the ‘Indonesia Emas 2045’ vision. Central Java had the highest prevalence of stunting among toddlers in Java Island in 2022 (20.8 percent), exceeding the WHO threshold (20 percent). This study aims to provide a general overview of the prevalence of stunting among toddlers and to identify the variables influencing it. The data used are secondary data from the Ministry of Health of the Republic of Indonesia, Statistics Indonesia (BPS), and the Health Office of Central Java, and were analyzed using multiple linear regression analysis. The results show that the variables of water and food management, food expenditure, and consumption of iron tablets have a significant negative effect on the prevalence of stunting among toddlers, while the percentage of teenage pregnancies and the percentage of toddlers with helminth infections have a significant positive effect on the prevalence of stunting among toddlers.